2015
DOI: 10.1128/cvi.00119-15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serial Skin Testing with Purified Protein Derivative on the Level and Quality of Antibodies to Complex and Defined Antigens in Mycobacterium bovis-Infected Cattle

Abstract: Bovine tuberculosis of cattle results primarily from infection with Mycobacterium bovis, a member of the Mycobacterium tuberculosis complex. Despite intensive control efforts, bovine tuberculosis persists as a costly disease, with adverse impacts on animal health and welfare, the trade of animals and animal products, and the livelihoods of producers. In addition, the persistence of this disease necessitates the maintenance of costly regional and federal networks for control/eradication campaigns. The mainstays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 41 publications
8
40
0
Order By: Relevance
“…Many studies have reported an anamnestic antibody response following skin testing in cattle and other species, including goats (2,27,(30)(31)(32)(33)(34)(35). Our data show that in 122 animals that received SIT in May 2014, the proportions that were anti-PPD-B antibody positive and the absolute levels of anti-PPD-B antibody 31 days after PPD-B injection were significantly higher than those observed 3 days after PPD-B injection, suggesting that some boosting had taken place 31 days following PPD-B administration.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported an anamnestic antibody response following skin testing in cattle and other species, including goats (2,27,(30)(31)(32)(33)(34)(35). Our data show that in 122 animals that received SIT in May 2014, the proportions that were anti-PPD-B antibody positive and the absolute levels of anti-PPD-B antibody 31 days after PPD-B injection were significantly higher than those observed 3 days after PPD-B injection, suggesting that some boosting had taken place 31 days following PPD-B administration.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research on bovine TB serology using enzyme-linked immunosorbent assay (ELISA), Western blotting, and MAPIA has demonstrated that (i) antibody responses to M. bovis involve multiple antigens, including MPB64, MPB70, MPB83, CFP10, and ESAT-6, with remarkable animal-to-animal variations in reactivity patterns (20); (ii) IgM and IgG antibodies can be detected in blood 3 to 4 and 4 to 6 weeks, respectively, after M. bovis inoculation (2, 17); (iii) individual seroreactivity profiles may evolve with disease progression (20); (iv) the variability and evolution of the humoral immune response may be addressed by use of multiantigen cocktails to maximize the diagnostic sensitivity of serological assays (17,20,25); (v) antibody responses in M. bovis-infected cattle are boosted following PPD injection for skin testing (3,25); and (vi) at advanced disease stages, antibody levels positively correlate with lesion severity (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were obtained from Holstein steers that had been aerosol infected with M. bovis (ϳ10 4 CFU of strain 95-1315 or 10-7428) in four experiments performed as described previously (2,3,31) in a biosafety level 3 (BSL-3) facility at the National Animal Disease Center, Ames, IA, in accordance with Institutional Biosafety and Animal Care and Use Committee guidelines. Serial samples were collected at multiple time points postinoculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those animals that react to PPD are isolated and slaughtered [11, 12]. Despite intensive eradication efforts over decades, bTB persists as a costly disease with adverse impacts on animal health and welfare, trade of animals and animal products, and livelihoods of producers, and continues to be a problem with global perspectives [4, 13]. It has been suggested that TST is a good herd test but a poor test for identifying individual infected animals [4].…”
Section: Introductionmentioning
confidence: 99%